Impact of electronic cigarette vaping on the cardiovascular function in young and old rats - Wangde Dai; Jianru Shi; Juan Carreno; Michael T. Kleinman; David A. Herman; Rebecca J. Arechavala; Samantha Renusch; Irene Hasen; Amanda Ting; Robert A. Kloner (Scientific Reports)
Abstract Background While the acute exposure to electronic cigarette (E-cig) vapor has been associated with an increase in blood pressure, the chronic effect of E-cig vapor on blood pressure compared to standard cigarette smoke has not been extensively studied. We determined the effect of E-cig exposure on blood pressure and other measures of cardiac function in both young and old rats. Methods Young Sprague Dawley rats (6 weeks old, both sexes) were randomly exposed to air (n = 34), E-cig with nicotine (E-cig Nic+; n = 30), E-cig without nicotine (E-cig Nic-; n = 28) or standard cigarette smoke (n = 27). Old Fischer 344 rats (25 months old, both sexes) were randomized into 2 groups: (1) 26 rats in the purified air (negative control) group and (2) 17 rats in the electronic cigarette vapor plus nicotine group (E-cig Nic+). After 12 weeks of exposure, hemodynamics were determined by Millar catheter, echocardiography, and thermodilution catheter, a few days after their last exposure. Results In young rats, cigarette smoke was associated with higher systolic, diastolic and mean blood pressures and peak LV systolic pressure, compared to air or E-cig Nic + or E-cig Nic- groups. Neither fractional shortening nor cardiac output differed among the groups. Absolute value for dp/dt min, a measure of diastolic LV function, was lowest in the E-cig Nic- group. Tau, a measure of LV relaxation was worse in this group as well. In old rats, E-cig vaping did not change heart rate, blood pressure, and cardiac function. However, E-cig Nic + exposure was associated with a greater heart weight/BW and LV weight/BW compared to air exposure in old rats. Conclusions Chronic exposure to E-cig vaping did not cause an increase in blood pressure or heart rate, nor did it change cardiac function compared to air in young rats after 12 weeks of exposure, while standard cigarette smoking was associated with an increase in blood pressure. E-cig vaping was associated with a greater heart weight/BW and LV weight/BW compared to air exposure in old rats, suggested that older animals might be more vulnerable to E-cig stimulus than younger ones.